2008
DOI: 10.5194/hess-12-383-2008
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of future climate change and sulphur emission reductions on acidification recovery at Plastic Lake, Ontario

Abstract: Abstract. Climate-induced drought events have a significant influence on sulphate export from forested catchments in central Ontario, subsequently delaying the recovery of surface waters from acidification. In the current study, a model chain that employed a statistical downscaling model, a hydrological model and two hydrochemical models was used to forecast the chemical recovery of Plastic Lake sub-catchment 1 (PC1) from acidification under proposed deposition reductions and the A2 emission scenario of the In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…An oxygen isotope study of the dissolved SO 4 2-in soil solution demonstrated that 32-61% of the SO 4 2-leaving the catchment had interacted with organic S in the soil (Gélineau et al 1989). Previous work at Plastic Lake (PC1) Watershed has indicated that sulfate export was strongly influenced by the presence of a large coniferSphagnum swamp (e.g., LaZerte 1993; Eimers and Dillon 2002;Eimers et al 2007;Aherne et al 2008). Stable isotopic analyses have shown that changes in SO 4 2-concentration at this watershed are associated with microbial redox processes (Eimers et al 2004a, b).…”
Section: Comparisons Of Sulfur Budget Differences Among Watershedsmentioning
confidence: 97%
“…An oxygen isotope study of the dissolved SO 4 2-in soil solution demonstrated that 32-61% of the SO 4 2-leaving the catchment had interacted with organic S in the soil (Gélineau et al 1989). Previous work at Plastic Lake (PC1) Watershed has indicated that sulfate export was strongly influenced by the presence of a large coniferSphagnum swamp (e.g., LaZerte 1993; Eimers and Dillon 2002;Eimers et al 2007;Aherne et al 2008). Stable isotopic analyses have shown that changes in SO 4 2-concentration at this watershed are associated with microbial redox processes (Eimers et al 2004a, b).…”
Section: Comparisons Of Sulfur Budget Differences Among Watershedsmentioning
confidence: 97%
“…SDSM has shown advantage over other statistical downscaling approaches such as weather generators and weather typing because of its better ability in describing inter-annual variability. It has widely been used throughout the world to downscale single-site scenarios of daily surface weather variables from predictors of GCMs for assessing hydrologic responses in climate change scenarios (Dibike and Coulibaly 2005;Gagnon et al 2005;Aherne et al 2008;Combalicer et al 2010;Huang et al 2011;Goyal et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The further control scenario combined with drought (scenario 3′) might reduce the SO 4 2− concentration to a level lower than in scenario 1. Recent studies also indicated that drought significantly affected SO 4 2− export from forested catchments, subsequently delaying the recovery of surface waters from acidification (Aherne et al, 2008;Evans et al, 1998;Larssen, 2005;Wright et al, 2006). Those studies emphasized that the reoxidation of sulfur stored in wetlands as sulfide caused episodic acidification during the rain events, which were strongly associated with preceding drought conditions (Aherne et al, 2008;Laudon et al, 2004).…”
Section: Forecast: Climate Scenariosmentioning
confidence: 95%
“…Recently, the effects of climate change and climate variation, especially climate-induced drought, on water acidification and recovery, have attracted considerable attention (e.g., Aherne et al, 2008;Bencokova et al, 2011;Evans et al, 1998;Kerr et al, 2011;Larssen, 2005;Laudon et al, 2004;Wright et al, 2006). Historical precipitation data showed drier summers and an increased frequency of droughts across southeastern China (Ren et al, 2005).…”
Section: Introductionmentioning
confidence: 97%